2014
DOI: 10.1177/1352458514546791
|View full text |Cite
|
Sign up to set email alerts
|

Cingulum bundle alterations underlie subjective fatigue in multiple sclerosis

Abstract: Our data point to the cingulum bundle and its projections as the key network involved in subjective fatigue perception in MS. More generally, these results suggest the potential of the connectionist framework to generate coherent models of the neural basis of complex symptomatology in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 37 publications
6
44
0
Order By: Relevance
“…A significant inverse correlation between FA and RD and limited changes in the AD values in patients with NMOSD compared to HCs suggest that the WM damage in NMOSD is related more to demyelination than to axonal degeneration. This is consistent with previous TBSS DTI studies, which showed widespread DTI metric changes and found that the lower FA was driven by higher RD in NMOSD .…”
Section: Discussionsupporting
confidence: 93%
“…A significant inverse correlation between FA and RD and limited changes in the AD values in patients with NMOSD compared to HCs suggest that the WM damage in NMOSD is related more to demyelination than to axonal degeneration. This is consistent with previous TBSS DTI studies, which showed widespread DTI metric changes and found that the lower FA was driven by higher RD in NMOSD .…”
Section: Discussionsupporting
confidence: 93%
“…Several lines of evidence suggest that atrophy as well as functional changes in the ACC are related to fatigue in MS patients ( 6 , 8 , 10 , 108 , 109 ). Multiple structural imaging studies found an association between increased white and gray matter atrophy in the ACC and subjective fatigue in MS patients ( 6 , 8 , 108 ). Furthermore, functional imaging studies found that MS patients with fatigue have a larger and more significant activation of the ACC during the execution of simple motor tasks than patients without fatigue ( 10 , 109 ).…”
Section: Studies On the Involvement Of The Insula The Anterior Cingumentioning
confidence: 99%
“…Despite the absence of a systematic pattern of cortical damage in MS (Kluckow, Rehbein, Schwab, Witte, & Bublak, 2016), significant atrophy has been repeatedly observed in interoceptive regions, such as the insula and the ACC (Lansley, Mataix-Cols, Grau, Radua, & Sastre-Garriga, 2013). Moreover, the heterogeneous patterns of white matter lesions in this condition include alterations in pathways of interoceptive areas, such as the ACC white matter bundle within the left cingulate fasciculus (Pardini et al, 2015). In the same vein, MS involves functional connectivity alterations across several regions (Faivre et al, 2012;Rocca et al, 2012Rocca et al, , 2015Roosendaal et al, 2010), crucially including both hypo-connectivity in the ACC (Rocca et al, 2015) and the insula (He et al, 2009), and hyper-connectivity in networks including these areas and the somatosensory cortex (SSC) (Faivre et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…b): Links indicate interregional connectivity. Indeed, the heterogeneous patterns of functional connectivity alterations in MS include abnormalities between interoceptive areas, such as the ACC and the insula(Faivre et al, 2012;Rocca et al, 2015;Roosendaal et al, 2010), alongside disruptions in relevant anatomical pathwaysfor example, the ACC white matter bundle within the left cingulate fasciculus (CruzGomez, Ventura Campos, Belenguer, Avila, & Forn, 2013;Pardini et al, 2015). Colors indicate statistically significant differences (p < .05; green = interoception > mind wandering; red = MS patients > controls; black = no significant differences).…”
mentioning
confidence: 99%